2022
DOI: 10.4314/mmj.v34i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of common mental disorders among children and adolescents in Blantyre-Urban, Malawi

Abstract: BackgroundThe high global prevalence of mental disorders justifies the need to quantify their burden in the sub-Saharan Africa where there is a dearth of information. These mental disorders are linked to different socio-demographic factors.ObjectiveTo determine the prevalence of, and factors associated with mental disorders among children and adolescents in Blantyre City, Malawi.Methods Children and adolescents aged 6 to 17 years were interviewed to determine their socio-demographic characteristics and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
5
2
Order By: Relevance
“…Another study on a Chinese population during the COVID-19 epidemic showed more depression and severe anxiety symptoms in females than males ( 41 ). However, these results are contrary to Matandika et al ( 12 ). Matandika et al ( 12 ) found that the prevalence of mental disorders was higher in males than in females.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Another study on a Chinese population during the COVID-19 epidemic showed more depression and severe anxiety symptoms in females than males ( 41 ). However, these results are contrary to Matandika et al ( 12 ). Matandika et al ( 12 ) found that the prevalence of mental disorders was higher in males than in females.…”
Section: Discussioncontrasting
confidence: 90%
“…However, these results are contrary to Matandika et al ( 12 ). Matandika et al ( 12 ) found that the prevalence of mental disorders was higher in males than in females. Hence, more research is needed in sub-Saharan Africa to understand the scale of adolescent mental health problems.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Existing research supports risk tiering and pediatric care coordination among children based on community-and household-level factors; however, such research is limited (Swann-Thomsen et al, 2021). Therefore, it is critical for providers to understand the context of the SDOH within the child's household and help connect them with appropriate resources to access necessary care (Fusar-Poli, 2019;Hodgkinson et al, 2017;Matandika et al, 2022). Recent literature emphasizes that screening for SDOH is ineffective without a supportive intervention to facilitate service connection (Dworkin & Garg, 2019;.…”
Section: Discussionmentioning
confidence: 99%